Aspirin for the prevention of preeclampsia: A systematic review and meta-analysis of randomized controlled studies - Wang, Yixiao; Guo, Xiaojun; Obore, Nathan; Ding, Hongjuan; Wu, Chengqian; Yu, Hong (Frontiers in Cardiovascular Medicine, 2022)
Background The results of randomized controlled studies on aspirin for the prevention of preeclampsia (PE) are conflicting, and some of the related meta-analyses also have limitations or flaws. Data sources A search was conducted on PubMed, Embase, and Cochrane Central Register of Controlled Trials databases, with no time or language restrictions. Study eligibility criteria Randomized controlled studies comparing aspirin for the prevention of PE were conducted. Methods Systematic reviews were performed according to the Cochrane Manual guidelines. A fixed-effects model or a random-effects model was chosen to calculate pooled relative risks with 95% confidence intervals based on the heterogeneity of the included studies. The study aimed to investigate the effect of aspirin on the development of PE in high-risk and general populations of women. Publication bias was assessed by funnel plots. All included studies were assessed for bias by the Cochrane Manual of Bias Assessment. Subgroup analyses were conducted on the aspirin dose, time of initial aspirin intervention, and the region in which the research was conducted, to explore the effective dose of aspirin and time of initial aspirin intervention and to try to find sources of heterogeneity and publication bias. Results A total of 39 articles were included, including 29 studies involving pregnant women at high risk for PE (20,133 patients) and 10 studies involving a general population of pregnant women (18,911 patients). Aspirin reduced the incidence of PE by 28% (RR 0.72, 95% CI 0.62–0.83) in women at high risk for PE. Aspirin reduced the incidence of PE by 30% in the general population (RR 0.70, 95% CI 0.52–0.95), but sensitivity analyses found that aspirin in the general population was not robust. A subgroup analysis showed that an aspirin dose of 75 mg/day (RR 0.50, 95% CI 0.32–0.78) had a better protective effect than other doses. Starting aspirin at 12–16 weeks (RR 0.62, 95% CI 0.53–0.74) of gestation or 17–28 weeks (RR 0.62, 95% CI 0.44–0.89) reduced the incidence of PE by 38% in women at high risk for PE, but the results were more reliable for use at 12–16 weeks. Heterogeneity and publication bias of the included studies may be mainly due to the studies completed in Asia. Conclusion Aspirin is recommended to be started at 12–16 weeks of pregnancy in women at high risk for PE. The optimal dose of aspirin to use is 75 mg/d. Systematic review registration [www.ClinicalTrials.gov], identifier [CRD42022319984].